On the elastic orthotropy - Blinowski, A.; Ostrowska-Maciejewska, J. (Archives of Mechanics, 1996)
Expressions for Kelvin moduli of orthotropic linearly elastic bodies in terms of Young's moduli and Poisson's ratios are presented. The check of the orthotropy criterion is posed as a variational problem.